Kinetics of Drug Release via Nicardipine Hydrochloride-loaded Carboxymethyl Cellulose/Poly(D,L-lactic-co-glycolic acid) Nanocarriers Using a Contemporary Emulsion Process - Nopparuj Soomherun (2020)
© 2020 Wiley-VCH GmbH A contemporary synthesis of polymeric nanocarriers based on drug delivery systems was employed using a water in oil in water (W1/O/W2) double emulsion process to develop nicardipine hydrochloride-loaded carboxymethyl cellulose/poly(D,L-lactic-co-glycolic acid) (NCH-CMC/PLGA) nanocarriers. The optimal synthesis of the nanocarriers was studied, including polymer amount, cross-linker concentration, and emulsifier concentration. The synthesized nanocarriers were smaller than ∼169 nm and showed a drug encapsulation of more than 80% and a yield of 51% to 73%. The NCH-CMC/PLGA nanocarriers presented good stability in aqueous dispersion for 10 days. Controlled drug release from the nanocarriers was slow and continuous for up to 16 days. The nanocarriers protected the drug against degradation and maintained therapeutic drug concentrations. In addition, the transport of drug release was studied via five conventional mathematical modelings such as Zero-order model, First-order model, Hixson-Crowell model, Higuchi model, and Korsmeyer-Peppas model. The Korsmeyer-Peppas model was fitted to achieve mathematical modeling for the optimized formulation of nanocarriers. Moreover, significant cytocompatibility was observed at all tested doses of NCH-CMC/PLGA nanocarriers. The NCH-CMC/PLGA nanocarriers could be an effective drug delivery agent for calcium channel blockers.